A yellow high borosilicate glass composition

By optimizing the formulation and process, a yellow borosilicate glass composition was developed, which solved the shortcomings of traditional glass masks in protecting harmful radiation from welding and achieved better radiation protection and service life.

CN118637823BActive Publication Date: 2025-02-07ZHUOLU TIANYUAN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411124221.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-02-07
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

Traditional black glass masks are not effective in protecting harmful radiation such as ultraviolet, infrared and blue light generated during welding, resulting in eye health problems for welders.

Method used

Using the optimized yellow borosilicate glass composition, the ratio of La2O3, CaO and ZnO is enhanced, and the chromium yellow PbCrO4 is used as the colorant, combined with heat treatment and gradient annealing process, the Na2O content and potassium salt bath treatment are improved, and the wear resistance of the glass is improved. , radiation resistance and optical properties.

Benefits of technology

It achieves the radiation protection ability of the glass, especially the filtration effect in the blue-violet light area, extends the service life and improves the welder's eye protection effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a yellow high borosilicate glass composition, which belongs to the technical field of borosilicate glass, and comprises the following raw materials by weight: 60-70 parts of SiO2, 10-15 parts of B2O3, 12.1-29 parts of reinforcing materials and several parts of yellow colorants; wherein the reinforcing materials include La2O3, CaO, ZnO, Al2O3, Na2O and MoO3. The present invention optimizes the formula to enhance the ratio of La2O3, CaO and ZnO, thereby improving the wear resistance of the glass. Chrome yellow PbCrO4 is used for coloring, which is both beautiful and strengthens ultraviolet and blue light filtering. Heat treatment and gradient annealing processes are set to ensure that the glass has high purity and strong light transmittance. Increasing the Na2O content achieves a good fluxing effect, promotes the transformation of the boron-oxygen structure, and enhances the uniformity of the glass. Molten potassium salt bath treatment, introduction of K + Forms a protective film to improve surface smoothness, scratch resistance and corrosion resistance, and comprehensively optimizes glass performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of borosilicate glass, and more specifically, to a yellow high-borosilicate glass composition. Background Art

[0002] In welding operations, it is crucial to protect welders' eyes from arc radiation. However, the black glass lenses used in traditional masks are obviously insufficient in terms of protection. Although these lenses can absorb some strong light, they cannot fully and effectively filter harmful radiation such as ultraviolet rays, infrared rays and blue light generated during welding. Long-term exposure can easily lead to serious health problems such as eye fatigue, burns and even cataracts.

[0003] With the advancement of material science, high borosilicate glass has been introduced into the field of welding goggles due to its excellent physical and chemical properties. High borosilicate glass has shown significant advantages in reducing dispersion and refractive index, improving the transmittance and clarity of light, and providing a clearer field of vision. However, despite the improvement in the overall performance of high borosilicate glass, the filtering effect in specific wavelength ranges, such as the blue-violet region, is still not ideal. This makes it difficult to achieve a good filtering effect while pursuing high clarity.

[0004] Therefore, it is necessary to develop a new type of borosilicate glass that can not only ensure high light transmittance and high clarity, but also have excellent radiation protection capabilities, especially in achieving significant breakthroughs in the filtering effect within harmful wavelengths such as blue and purple light. Summary of the invention

[0005] In order to solve the problems raised in the background technology, the present application provides a yellow high borosilicate glass composition. The present invention optimizes the formula, enhances the ratio of La2O3, CaO, and ZnO, and improves the wear resistance of the glass. The use of chrome yellow PbCrO4 for coloring is both beautiful and strengthens ultraviolet and blue light filtering. Heat treatment and gradient annealing processes are set to ensure that the glass is high in purity and has strong light transmittance. Increasing the Na2O content achieves a good fluxing effect, promotes the transformation of the boron-oxygen structure, and enhances the uniformity of the glass. Molten potassium salt bath treatment introduces K + Forms a protective film to improve surface smoothness, scratch resistance and corrosion resistance, and comprehensively optimizes glass performance.

[0006] The present application provides a yellow high borosilicate glass composition, which adopts the following technical solution:

[0007] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0008] 60-70 parts SiO2, 10-15 parts B2O3, 14.1-29 parts reinforcing material;

[0009] The reinforcing material includes 2-4 parts of La2O3, 5-8 parts of CaO, 3-5 parts of ZnO, 0.1-1 parts of Al2O3, 3-8 parts of Na2O and 1-3 parts of MoO3;

[0010] The yellow high borosilicate glass composition further includes a yellow colorant.

[0011] Furthermore, the yellow colorant is chromate, and preferably, the chromate is chrome yellow.

[0012] Furthermore, the specific preparation method of the yellow high borosilicate glass comprises the following steps:

[0013] S1, mixing the raw materials of the formula, crushing, grinding and screening, then adding deionized water to the powder, stirring and then performing melting heat treatment to prepare a glass melt;

[0014] S2, transferring the molten glass into a stainless steel glass mold and performing annealing treatment to obtain rough glass;

[0015] S3. Grind, polish and wash the rough glass to obtain a yellow high-borosilicate glass.

[0016] Furthermore, the specific preparation method of the yellow high borosilicate glass comprises the following steps:

[0017] S1. Mix the raw materials of the formula, crush and grind them to pass through a 200-mesh sieve, then add 3-5wt% deionized water to the powder, stir for 3-5 minutes, and then perform melting heat treatment to prepare a glass melt;

[0018] S2, transferring the molten glass into a stainless steel glass mold and performing annealing treatment to obtain rough glass;

[0019] S3. Grind and polish the rough glass, and wash it with deionized water to obtain a yellow high-borosilicate glass.

[0020] Furthermore, in step S1, the specific operation of the melt heat treatment is:

[0021] The system temperature is raised to 1450-1600°C at a heating rate of 10-20°C / min, and the melting time is 2-7 hours.

[0022] Further, in step S2, the annealing treatment comprises the following steps:

[0023] The system temperature is lowered to 850-950°C at a rate of 5-10°C / min, kept at this temperature for 2-3 hours, and then further lowered to 400-450°C at a rate of 10-20°C / min, kept in a molten salt bath of potassium salt for 0.5-1 hour, and then naturally cooled to room temperature.

[0024] Furthermore, the usage amount of the yellow colorant is 1-5wt% of the total mass of SiO2, B2O3 and the reinforcing material.

[0025] Furthermore, in step S3, the rough glass is ground and polished, and the specific operation of washing is as follows:

[0026] The rough glass is coarsely ground with a diamond grinding wheel at a coarse grinding rate of 1500-2000 rpm, and then polished; the polished glass is placed in an ultrasonic cleaner, cleaned with a neutral detergent and deionized water, rinsed and air-dried to obtain a yellow high borosilicate glass.

[0027] In summary, this application has the following beneficial effects:

[0028] In the technical solution of the present invention, by optimizing the proportion of reinforcing materials in the formula, especially increasing the content of oxides such as La2O3, CaO, and ZnO in appropriate amounts, these oxides can form a stable crystal structure at high temperatures, effectively enhancing the density and hardness of the glass, thereby significantly improving the wear resistance of the glass surface. Even in the case of frequent friction or scratching, the surface finish can be maintained and the service life can be extended.

[0029] In the technical solution of the present invention, the chrome yellow PbCrO4 used as a yellow colorant not only gives the glass a distinct yellow hue, but also has good thermal stability at high temperatures and is not easy to decompose or discolor. The stability of chrome yellow ensures the consistency and stability of the color of the glass during the high-temperature production process and use. At high temperatures, chrome yellow also absorbs and scatters ultraviolet light and blue light through its unique chemical structure, thereby achieving uniform absorption of light and achieving an effective filtering effect.

[0030] In the technical solution of the present invention, the glass raw materials are fully mixed and evenly melted by fine grinding and melting heat treatment with temperature gradient annealing and molten potassium salt bath, which reduces internal defects and impurities. This not only improves the optical transmittance of the glass, but also makes the light clearer when passing through the glass, reduces scattering and blurring, and improves the overall optical performance.

[0031] In addition, the present invention uses a large amount of Na2O components in the formula of the glass composition. Therefore, during the heat treatment and annealing process, the presence of sodium element can improve the melting effect of the glass composition, promote the melting of the components, and provide free oxygen to destroy the silicon-oxygen skeleton structure, so that the boron-oxygen triangle [BO3] is transformed into a boron-oxygen tetrahedron [BO4], and the structure of boron is transformed from a layered structure to a frame structure, providing an opportunity for B2O3 and SiO2 to recombine, which is conducive to forming a uniform glass. Subsequently, a potassium salt molten salt bath is used for heat preservation treatment, and the Na on the surface of the material is + The ions will react with the K +The ions are exchanged to reduce the Na content in the material, thus avoiding the problem of decreased mechanical properties of the glass material due to excessive Na content. + Due to the large ion radius, the ions in potassium salt can penetrate into the glass surface to form a protective film. This protective film not only introduces compressive stress on the glass surface, improves the smoothness and flatness of the glass surface, but also significantly enhances its scratch resistance and corrosion resistance. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The polishing liquid used in the following examples and comparative examples is diamond polishing liquid, and the diamond particle size is 3 μm.

[0034] Example 1

[0035] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0036] 60 parts of SiO2, 10 parts of B2O3, 14.1 parts of reinforcing materials and yellow colorant;

[0037] Among them, the reinforcing materials include 2 parts of La2O3, 5 parts of CaO, 3 parts of ZnO, 0.1 parts of Al2O3, 3 parts of Na2O and 1 part of MoO3.

[0038] Among them, the yellow colorant is PbCrO4, and the usage amount is 1wt% of the total mass of SiO2, B2O3 and reinforcing materials.

[0039] The specific preparation method of yellow high borosilicate glass comprises the following steps:

[0040] S1. Mix the raw materials of the formula, crush and grind them through a 200-mesh sieve, then add 3 wt % deionized water to the powder, stir for 3 minutes, and then perform melting heat treatment. Raise the system temperature to 1450° C. at a heating rate of 10° C. / min. The melting time is 2 hours to prepare a glass melt;

[0041] S2, transferring the glass melt into a stainless steel glass mold, performing annealing treatment, reducing the system temperature to 850°C at a rate of 5°C / min, and keeping it warm for 2 hours, then further reducing the temperature to 400°C at a rate of 10°C / min, and keeping it warm in a molten salt bath of potassium nitrate for 0.5 hours, and then naturally cooling it to room temperature to obtain a rough glass;

[0042] S3. The rough glass is preliminarily ground using a diamond wheel with a grit of 80 meshes at a rough grinding rate of 1500 rpm. After 10 minutes, a diamond wheel with a grit of 200 meshes is replaced and grinding is continued to reduce the surface roughness. The polishing liquid and the polishing wheel are used and polished at a speed of 1000 rpm for 15 minutes. The polished glass is placed in an ultrasonic cleaner with an ultrasonic cleaning frequency of 40 kHz. A neutral detergent and deionized water are used for cleaning. The mass percentage concentration of the neutral detergent is 4.5%. The cleaning time is 120 seconds. The deionized water cleaning time is 180 seconds and the cleaning temperature is 65°C. The glass is then thoroughly rinsed with deionized water and air-dried to obtain a yellow high-borosilicate glass.

[0043] Example 2

[0044] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0045] 65 parts of SiO2, 13 parts of B2O3, 20.5 parts of reinforcing materials and yellow colorant;

[0046] Among them, the reinforcing materials include 3 parts of La2O3, 6 parts of CaO, 4 parts of ZnO, 0.5 parts of Al2O3, 5 parts of Na2O and 2 parts of MoO3.

[0047] Among them, the yellow colorant is PbCrO4, and the usage amount is 3wt% of the total mass of SiO2, B2O3 and reinforcing materials.

[0048] The specific preparation method of yellow high borosilicate glass comprises the following steps:

[0049] S1. Mix the raw materials of the formula, crush and grind them through a 200-mesh sieve, then add 4 wt % deionized water to the powder, stir for 4 minutes, and then perform melting heat treatment. Raise the system temperature to 1500° C. at a heating rate of 15° C. / min. The melting time is 5 hours to prepare a glass melt;

[0050] S2, transferring the glass melt into a stainless steel glass mold for annealing treatment, reducing the system temperature to 900°C at a rate of 7°C / min, keeping it warm for 2.5 hours, then further reducing the temperature to 430°C at a rate of 15°C / min, and keeping it warm in a molten salt bath of potassium nitrate for 0.8 hours, and then naturally cooling it to room temperature to obtain a rough glass;

[0051] S3, grinding and polishing the rough glass, and the specific operation of washing is as follows:

[0052] The rough glass is preliminarily ground using a diamond wheel with a particle size of 100 meshes at a rough grinding rate of 1700 rpm. After 10 minutes, the diamond wheel with a particle size of 200 meshes is replaced and the grinding is continued to reduce the surface roughness. The polishing liquid and the polishing wheel are used and polished at a speed of 1000 rpm for 15 minutes. The polished glass is placed in an ultrasonic cleaner with an ultrasonic cleaning frequency of 40 kHz. It is cleaned with a neutral detergent and deionized water with a mass percentage concentration of the neutral detergent of 4.5%. The cleaning time is 120 seconds, the deionized water cleaning time is 180 seconds, and the cleaning temperature is 65°C. It is then thoroughly rinsed with deionized water and air-dried to obtain a yellow high-borosilicate glass.

[0053] Example 3

[0054] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0055] 70 parts of SiO2, 15 parts of B2O3, 29 parts of reinforcing materials and yellow colorant;

[0056] Among them, the reinforcing materials include 4 parts of La2O3, 8 parts of CaO, 5 parts of ZnO, 1 part of Al2O3, 8 parts of Na2O and 3 parts of MoO3.

[0057] Among them, the yellow colorant is PbCrO4, and the usage amount is 5wt% of the total mass of SiO2, B2O3 and reinforcing materials.

[0058] The specific preparation method of yellow high borosilicate glass comprises the following steps:

[0059] S1. Mix the raw materials of the formula, crush and grind them through a 200-mesh sieve, then add 5 wt% deionized water to the powder, stir for 5 minutes, and then perform melting heat treatment. Raise the system temperature to 1600° C. at a heating rate of 20° C. / min. The melting time is 7 hours to prepare a glass melt;

[0060] S2, transferring the molten glass to a stainless steel glass mold for annealing treatment, reducing the system temperature to 950°C at a rate of 10°C / min, and keeping it warm for 3 hours, then further reducing the temperature to 450°C at a rate of 20°C / min, and keeping it warm in a molten salt bath of potassium nitrate for 1 hour, and then naturally cooling it to room temperature to obtain a rough glass;

[0061] S3, grinding and polishing the rough glass, and the specific operation of washing is as follows:

[0062] The rough glass is preliminarily ground using a diamond wheel with a particle size of 120 at a rough grinding rate of 2000 rpm. After 10 minutes, the diamond wheel with a particle size of 200 is replaced and the grinding is continued to reduce the surface roughness. The polishing liquid and the polishing wheel are used and polished at a speed of 1000 rpm for 15 minutes. The polished glass is placed in an ultrasonic cleaner with an ultrasonic cleaning frequency of 40 kHz. It is cleaned with a neutral detergent and deionized water with a mass percentage concentration of the neutral detergent of 4.5%. The cleaning time is 120 seconds, the deionized water cleaning time is 180 seconds, and the cleaning temperature is 65°C. It is then thoroughly rinsed with deionized water and air-dried to obtain a yellow high-borosilicate glass.

[0063] Comparative Example 1

[0064] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0065] 60 parts of SiO2, 10 parts of B2O3, 14.1 parts of reinforcing materials and yellow colorant;

[0066] Among them, the reinforcing materials include 2 parts of La2O3, 5 parts of CaO, 3 parts of ZnO, 0.1 parts of Al2O3, 3 parts of Na2O and 1 part of MoO3.

[0067] Among them, the yellow colorant is Fe2O3, and the usage amount is 1wt% of the total mass of SiO2, B2O3 and reinforcing materials.

[0068] The specific preparation method of yellow high borosilicate glass comprises the following steps:

[0069] S1. Mix the raw materials of the formula, crush and grind them through a 200-mesh sieve, then add 3 wt % deionized water to the powder, stir for 3 minutes, and then perform melting heat treatment. Raise the system temperature to 1450° C. at a heating rate of 10° C. / min. The melting time is 2 hours to prepare a glass melt;

[0070] S2, transferring the glass melt into a stainless steel glass mold, performing annealing treatment, reducing the system temperature to 850°C at a rate of 5°C / min, and keeping it warm for 2 hours, then further reducing the temperature to 400°C at a rate of 10°C / min, and keeping it warm in a molten salt bath of potassium nitrate for 0.5 hours, and then naturally cooling it to room temperature to obtain a rough glass;

[0071] S3. The rough glass is preliminarily ground using a diamond wheel with a grit of 80 meshes at a rough grinding rate of 1500 rpm. After 10 minutes, a diamond wheel with a grit of 200 meshes is replaced and grinding is continued to reduce the surface roughness. The polishing liquid and the polishing wheel are used and polished at a speed of 1000 rpm for 15 minutes. The polished glass is placed in an ultrasonic cleaner with an ultrasonic cleaning frequency of 40 kHz. A neutral detergent and deionized water are used for cleaning. The mass percentage concentration of the neutral detergent is 4.5%. The cleaning time is 120 seconds. The deionized water cleaning time is 180 seconds and the cleaning temperature is 65°C. The glass is then thoroughly rinsed with deionized water and air-dried to obtain a yellow high-borosilicate glass.

[0072] Comparative Example 2

[0073] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0074] 60 parts of SiO2, 10 parts of B2O3, 12.1 parts of reinforcing materials and yellow colorant;

[0075] Among them, the reinforcing materials include 2 parts of La2O3, 5 parts of CaO, 3 parts of ZnO, 0.1 parts of Al2O3, 1 part of Na2O and 1 part of MoO3.

[0076] Among them, the yellow colorant is PbCrO4, and the usage amount is 1wt% of the total mass of SiO2, B2O3 and reinforcing materials.

[0077] The specific preparation method of yellow high borosilicate glass comprises the following steps:

[0078] S1. Mix the raw materials of the formula, crush and grind them through a 200-mesh sieve, then add 3 wt % deionized water to the powder, stir for 3 minutes, and then perform melting heat treatment. Raise the system temperature to 1450° C. at a heating rate of 10° C. / min. The melting time is 2 hours to prepare a glass melt;

[0079] S2, transferring the glass melt into a stainless steel glass mold, performing annealing treatment, reducing the system temperature to 850°C at a rate of 5°C / min, and keeping it warm for 2 hours, then further reducing the temperature to 400°C at a rate of 10°C / min, and keeping it warm in a molten salt bath of potassium nitrate for 0.5 hours, and then naturally cooling it to room temperature to obtain a rough glass;

[0080] S3. The rough glass is preliminarily ground using a diamond wheel with a grit of 80 meshes at a rough grinding rate of 1500 rpm. After 10 minutes, a diamond wheel with a grit of 200 meshes is replaced and grinding is continued to reduce the surface roughness. The polishing liquid and the polishing wheel are used and polished at a speed of 1000 rpm for 15 minutes. The polished glass is placed in an ultrasonic cleaner with an ultrasonic cleaning frequency of 40 kHz. A neutral detergent and deionized water are used for cleaning. The mass percentage concentration of the neutral detergent is 4.5%. The cleaning time is 120 seconds. The deionized water cleaning time is 180 seconds and the cleaning temperature is 65°C. The glass is then thoroughly rinsed with deionized water and air-dried to obtain a yellow high-borosilicate glass.

[0081] Comparative Example 3

[0082] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0083] 60 parts of SiO2, 10 parts of B2O3, 14.1 parts of reinforcing materials and yellow colorant;

[0084] Among them, the reinforcing materials include 2 parts of La2O3, 5 parts of CaO, 3 parts of ZnO, 0.1 parts of Al2O3, 3 parts of Na2O and 1 part of MoO3.

[0085] Among them, the yellow colorant is PbCrO4, and the usage amount is 1wt% of the total mass of SiO2, B2O3 and reinforcing materials.

[0086] The specific preparation method of yellow high borosilicate glass comprises the following steps:

[0087] S1. Mix the raw materials of the formula, crush and grind them through a 200-mesh sieve, then add 3 wt % deionized water to the powder, stir for 3 minutes, and then perform melting heat treatment. Raise the system temperature to 1450° C. at a heating rate of 10° C. / min. The melting time is 2 hours to prepare a glass melt;

[0088] S2, transferring the glass melt into a stainless steel glass mold, performing annealing treatment, reducing the system temperature to 400°C at a rate of 5°C / min, keeping the temperature for 2.5 hours, and then naturally cooling to room temperature to obtain a rough glass;

[0089] S3. The rough glass is preliminarily ground using a diamond wheel with a grit of 80 meshes at a rough grinding rate of 1500 rpm. After 10 minutes, a diamond wheel with a grit of 200 meshes is replaced and grinding is continued to reduce the surface roughness. The polishing liquid and the polishing wheel are used and polished at a speed of 1000 rpm for 15 minutes. The polished glass is placed in an ultrasonic cleaner with an ultrasonic cleaning frequency of 40 kHz. A neutral detergent and deionized water are used for cleaning. The mass percentage concentration of the neutral detergent is 4.5%. The cleaning time is 120 seconds. The deionized water cleaning time is 180 seconds and the cleaning temperature is 65°C. The glass is then thoroughly rinsed with deionized water and air-dried to obtain a yellow high-borosilicate glass.

[0090] Comparative Example 4

[0091] The difference between this comparative example and Example 1 is that K + Molten salt bath.

[0092] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0093] 60 parts of SiO2, 10 parts of B2O3, 14.1 parts of reinforcing materials and yellow colorant;

[0094] Among them, the reinforcing materials include 2 parts of La2O3, 5 parts of CaO, 3 parts of ZnO, 0.1 parts of Al2O3, 3 parts of Na2O and 1 part of MoO3.

[0095] Among them, the yellow colorant is PbCrO4, and the usage amount is 1wt% of the total mass of SiO2, B2O3 and reinforcing materials.

[0096] The specific preparation method of yellow high borosilicate glass comprises the following steps:

[0097] S1. Mix the raw materials of the formula, crush and grind them through a 200-mesh sieve, then add 3 wt % deionized water to the powder, stir for 3 minutes, and then perform melting heat treatment. Raise the system temperature to 1450° C. at a heating rate of 10° C. / min. The melting time is 2 hours to prepare a glass melt;

[0098] S2, transferring the glass melt into a stainless steel glass mold for annealing treatment, reducing the system temperature to 850°C at a rate of 5°C / min, keeping it at that temperature for 2 hours, and then further reducing the temperature to 400°C at a rate of 10°C / min, keeping it at that temperature for 0.5 hours, and then naturally cooling it to room temperature to obtain a rough glass;

[0099] S3. The rough glass is preliminarily ground using a diamond wheel with a grit of 80 meshes at a rough grinding rate of 1500 rpm. After 10 minutes, a diamond wheel with a grit of 200 meshes is replaced and grinding is continued to reduce the surface roughness. The polishing liquid and the polishing wheel are used and polished at a speed of 1000 rpm for 15 minutes. The polished glass is placed in an ultrasonic cleaner with an ultrasonic cleaning frequency of 40 kHz. A neutral detergent and deionized water are used for cleaning. The mass percentage concentration of the neutral detergent is 4.5%. The cleaning time is 120 seconds. The deionized water cleaning time is 180 seconds and the cleaning temperature is 65°C. The glass is then thoroughly rinsed with deionized water and air-dried to obtain a yellow high-borosilicate glass.

[0100] Comparative Example 5

[0101] A yellow high borosilicate glass composition, comprising the following raw materials in parts by weight:

[0102] 60 parts of SiO2, 10 parts of B2O3, 14.1 parts of reinforcing materials and yellow colorant;

[0103] Among them, the reinforcing materials include 2 parts of La2O3, 5 parts of CaO, 3 parts of ZnO, 0.1 parts of Al2O3 and 3 parts of Na2O.

[0104] Among them, the yellow colorant is PbCrO4, and the usage amount is 1wt% of the total mass of SiO2, B2O3 and reinforcing materials.

[0105] The specific preparation method of yellow high borosilicate glass comprises the following steps:

[0106] S1. Mix the raw materials of the formula, crush and grind them through a 200-mesh sieve, then add 3 wt % deionized water to the powder, stir for 3 minutes, and then perform melting heat treatment. Raise the system temperature to 1450° C. at a heating rate of 10° C. / min. The melting time is 2 hours to prepare a glass melt;

[0107] S2, transferring the glass melt into a stainless steel glass mold, performing annealing treatment, reducing the system temperature to 850°C at a rate of 5°C / min, and keeping it warm for 2 hours, then further reducing the temperature to 400°C at a rate of 10°C / min, and keeping it warm in a molten salt bath of potassium nitrate for 0.5 hours, and then naturally cooling it to room temperature to obtain a rough glass;

[0108] S3. The rough glass is preliminarily ground using a diamond wheel with a grit of 80 meshes at a rough grinding rate of 1500 rpm. After 10 minutes, a diamond wheel with a grit of 200 meshes is replaced and grinding is continued to reduce the surface roughness. The polishing liquid and the polishing wheel are used and polished at a speed of 1000 rpm for 15 minutes. The polished glass is placed in an ultrasonic cleaner with an ultrasonic cleaning frequency of 40 kHz. A neutral detergent and deionized water are used for cleaning. The mass percentage concentration of the neutral detergent is 4.5%. The cleaning time is 120 seconds. The deionized water cleaning time is 180 seconds and the cleaning temperature is 65°C. The glass is then thoroughly rinsed with deionized water and air-dried to obtain a yellow high-borosilicate glass.

[0109] Performance Testing

[0110] Now, the performance of the high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-5 is tested. Samples with a thickness of 5 mm and a width of 50 mm are prepared. Referring to the test methods in GB / T 34843-2017 and GB / T 37780-2019, the appearance, linear thermal expansion coefficient (20-300°C), Poisson's ratio, shear modulus and elastic modulus of the samples prepared in different groups are tested. In the shear modulus, the value of the correction parameter is 1.7. The surface hardness of the samples in different groups is tested using a microhardness tester. Each sample is tested 5 times, and the average value is recorded.

[0111] Among them, the appearance grade is evaluated according to the following standards:

[0112] A-level:

[0113] Transparency: Completely transparent, with no obvious turbidity or opaque areas.

[0114] Bubbles: No bubbles visible to the naked eye or very few tiny bubbles (< 0.1 mm) that do not affect the overall appearance and use.

[0115] Streaks: No visible streaks.

[0116] Color: Uniform color, without any color difference or color variation.

[0117] Surface defects: No scratches, cracks, bumps or other surface defects.

[0118] B-level:

[0119] Transparency: Good transparency, may be slightly turbid but not obvious.

[0120] Bubbles: There are a small number of bubbles visible to the naked eye, but the diameter does not exceed 0.5 mm, and the number of bubbles per square centimeter does not exceed 1.

[0121] Streaks: Minor visible streaks may be present.

[0122] Color: The color is basically uniform, with slight color difference.

[0123] Surface defects: Minor scratches or other surface defects.

[0124] C-level:

[0125] Transparency: Medium transparency, there may be obvious turbid areas, but the overall transparency is still visible.

[0126] Bubbles: There are obvious bubbles with a diameter not exceeding 1 mm and the number of bubbles per square centimeter not exceeding 3.

[0127] Streaks: Noticeable streaks.

[0128] Color: There is obvious color difference or mixed color.

[0129] Surface defects: There are obvious scratches or other surface defects.

[0130] D-level:

[0131] Transparency: Transparency is poor, with obvious turbid or opaque areas.

[0132] Bubbles: There are a large number of bubbles, with a diameter exceeding 1 mm and more than 3 bubbles per square centimeter.

[0133] Streaks: There are obvious streaks that affect appearance and use.

[0134] Color: The color is uneven, with obvious color difference or mottled colors.

[0135] Surface defects: There are serious scratches, cracks, unevenness or other significant surface defects that affect use.

[0136] The specific test results are shown in Table 1 below.

[0137] Table 1 Performance test of high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-5

[0138]

[0139] From the results shown in Table 1 above, it can be seen that the high borosilicate glass sample prepared in Example 2 shows the best performance. From the results in Comparative Example 1, it can be seen that the stability of the Fe2O3 colorant decreases during product preparation and temperature gradient annealing, which affects the linear thermal expansion coefficient, elastic modulus and other properties of the product. From the results in Comparative Example 4, it can be seen that after the molten salt bath, the elastic modulus, shear modulus and surface hardness of the obtained high borosilicate glass product are improved. The comprehensive performance of the high borosilicate glass prepared in Examples 1-3 of the present application is significantly better than that of the products prepared in Comparative Examples 1-5, that is, within the technical solution defined in the present application, the comprehensive performance of the obtained high borosilicate glass is excellent.

[0140] Now the filtering effect of the high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-5 is tested. The filtering effect of the high borosilicate glass prepared in different groups is tested with reference to the method described in GB / T 15489.6-2010. Take a sample of 100mm×100mm×5mm, use CIE standard light source D65 and a visible light spectrophotometer to measure the optical transmittance of the glass, place the samples prepared in different groups in the optical path of the spectrophotometer, measure its transmission spectrum in the wavelength range of 400nm to 700nm, record the transmittance changes of blue-violet light (400nm to 500nm) and green light (500nm to 570nm), and judge the filtering effect of the high borosilicate glass. The test results are shown in Table 2 below.

[0141] Table 2 Test of the filtering effect of the high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-5

[0142]

[0143] It can be seen from the results in Table 2 that the glass prepared in Example 2 has the best effect of filtering blue-violet light, and the visible light projection effect is moderate. It can be seen from the results in Comparative Example 1 that the PbCrO4 yellow colorant used in the present invention can play a better filtering effect in the product and effectively filter out light of a specific wavelength. It can be seen from the results in Comparative Example 2 that increasing the content of Na2O in the formula can better promote the fusion of the components in the glass composition and improve the visible light transmittance of the glass. It can be seen from the results in Comparative Example 5 that adding molybdenum oxide to the glass composition formula can improve the blue-violet light transmittance, which is beneficial to improving the filtering effect.

[0144] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

Claims

1. A yellow high borosilicate glass composition, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of SiO2, 10-15 parts of B2O3, and 14.1-29 parts of reinforcing material; The reinforcing material includes 2-4 parts of La2O3, 5-8 parts of CaO, 3-5 parts of ZnO, 0.1-1 parts of Al2O3, 3-8 parts of Na2O and 1-3 parts of MoO3; The yellow high borosilicate glass composition further includes a yellow colorant, and the yellow colorant is PbCrO4; The specific preparation method of the yellow high borosilicate glass comprises the following steps: S1, mixing the raw materials of the formula, crushing, grinding and screening, then adding deionized water to the powder, stirring and then performing melting heat treatment to prepare a glass melt; S2, transferring the glass melt into a stainless steel glass mold, performing annealing treatment, reducing the system temperature to 850-950°C at a rate of 5-10°C / min, keeping it warm for 2-3 hours, and then further reducing the temperature to 400-450°C at a rate of 10-20°C / min, and keeping it warm in a molten salt bath of potassium salt for 0.5-1 hour, and then naturally cooling to room temperature to obtain rough glass; S3. Grind, polish and wash the rough glass to obtain a yellow high-borosilicate glass.

2. A yellow high borosilicate glass composition according to claim 1, characterized in that: In step S1, the specific operation of melt heat treatment is: The system temperature is raised to 1450-1600°C at a heating rate of 10-20°C / min, and the melting time is 2-7 hours.

3. A yellow high borosilicate glass composition according to claim 1, characterized in that: The amount of the yellow colorant used is 1-5wt% of the total mass of SiO2, B2O3 and the reinforcing material.

4. A yellow high borosilicate glass composition according to claim 3, characterized in that: In step S3, the rough glass is ground and polished, and the specific operation of washing is as follows: The rough glass is coarsely ground with a diamond grinding wheel at a coarse grinding rate of 1500-2000 rpm, and then polished; the polished glass is placed in an ultrasonic cleaner, cleaned with a neutral detergent and deionized water, rinsed and air-dried to obtain a yellow high borosilicate glass.

Citation Information

Patent Citations

  • Ultraviolet and infrared radiation absorbing glass

    EP0834481A1